Flexible Threshold Quantum Homomorphic Encryption on Quantum Networks - Yongli Tang; Menghao Guo; Binyong Li; Kaixin Geng; Jinxia Yu; Baodong Qin (Entropy)
Currently, most quantum homomorphic encryption (QHE) schemes only allow a single evaluator (server) to accomplish computation tasks on encrypted data shared by the data owner (user). In addition, the quantum computing capability of the evaluator and the scope of quantum computation it can perform are usually somewhat limited, which significantly reduces the flexibility of the scheme in quantum network environments. In this paper, we propose a novel <semantics>(t,<mspace width="4.pt"></mspace>n)</semantics>-threshold QHE (TQHE) network scheme based on the Shamir secret sharing protocol, which allows <semantics>k<mspace width="4.pt"></mspace>(t≤k≤n)</semantics> evaluators to collaboratively perform evaluation computation operations on each qubit within the shared encrypted sequence. Moreover, each evaluator, while possessing the ability to perform all single-qubit unitary operations, is able to perform arbitrary single-qubit gate computation task assigned by the data owner. We give a specific (3, 5)-threshold example, illustrating the scheme’s correctness and feasibility, and simulate it on IBM quantum computing cloud platform. Finally, it is shown that the scheme is secure by analyzing encryption/decryption private keys, ciphertext quantum state sequences during transmission, plaintext quantum state sequence, and the result after computations on the plaintext quantum state sequence.